Pengaruh Debt To Equity Ratio, Kebijakan Dividen Dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Pt Pertamina (Persero) Tbk Periode 2015-2024 - Amira Kamaliya; Sutiman Sutiman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aims to analyze the effect of Debt to Equity Ratio, dividend policy, and firm size on earnings management at PT Pertamina (Persero) Tbk for the period 2015–2024. This research employs a quantitative method. The sample was obtained by compiling secondary data, namely the balance sheets and income statements of PT Pertamina (Persero) Tbk for the period 2015–2024. The data analysis techniques used include classical assumption tests, descriptive statistics, multiple linear regression analysis, and hypothesis testing using SPSS software version 27. The results indicate that the Debt to Equity Ratio does not have a significant effect on Earnings Management, with a t-value of -1.516 and a significance value of 0.180 > 0.005. Dividend Policy has a significant effect on Earnings Management, with a t-value of -1.112 and a significance value of 0.008 < 0.005. Meanwhile, Firm Size does not have a significant effect on Earnings Management, with a t-value of -0.529 and a significance value of 0.113 < 0.005. Simultaneously, Debt to Equity Ratio, Dividend Policy, and Firm Size have an effect on Earnings Management, with an F-value of 7.351 and a significance value of 0.020 > 0.050. The coefficient of determination (R²) of 100% indicates that all variations in Earnings Management can be explained by the three independent variables in this research model, while the remaining 0% is influenced by other factors outside the model.